“Jean Barman — Vernacular Historian” - Devine, Heather (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2016)
Over the past year, several excellent new publications focused on the histories of mixed-race French-Canadian communities in western Canada and the Pacific Northwest. Of these books, Jean Barman’s French Canadians, Furs and Indigenous Women in the Making of the Pacific Northwest merits special attention, because the author has successfully sought out, and integrated, vernacular voices as historical sources. And for this reason, Jean Barman is sometimes referred to as a “vernacular,” or grassroots historian. What is vernacular history? Is this genre a product of methodology or of one’s worldview? And can a vernacular approach to history help scholars navigate the increasingly politicised environment of indigenous studies? The author reflects on these questions, by sharing some of her personal experiences with Jean Barman that illustrate the complexity of the issues surrounding indigenous historical practice today.